2012
DOI: 10.1063/1.3684833
|View full text |Cite
|
Sign up to set email alerts
|

Energy harvesting in semiconductor-insulator-semiconductor junctions through excitation of surface plasmon polaritons

Abstract: We have demonstrated a simple approach for developing a photovoltaic device consisting of semiconductor-insulator-semiconductor (SIS) heterojunction using surface plasmon polaritons (SPPs) generated in one of the semiconductors (Al:ZnO) and propagated through the dielectric barrier (SiO2) to other (Si). This robust architecture based on surface plasmon excitation within an SIS device that produces power based on spatial confinement of electron excitation through plasmon absorption in Al:ZnO in a broad spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…[1][2][3] The unique combination of metallicity and transparency makes TCOs appealing for a variety of applications, [4][5][6][7] including photovoltaic cells, flat displays, smart windows, invisible electronics and plasmonics. [9][10][11][12] The optoelectronic performances of TCOs strictly depend on the quality of the samples and on the growth techniques. 8 AZO in particular is gaining great interest as it is an indium-free, low-cost, and easy processable material.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The unique combination of metallicity and transparency makes TCOs appealing for a variety of applications, [4][5][6][7] including photovoltaic cells, flat displays, smart windows, invisible electronics and plasmonics. [9][10][11][12] The optoelectronic performances of TCOs strictly depend on the quality of the samples and on the growth techniques. 8 AZO in particular is gaining great interest as it is an indium-free, low-cost, and easy processable material.…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the role of UV absorption in photoresponsivity of AZO-based solar cell, we have fabricated an n-AZO/p-Si heterostructure diode and measured its photoresponsivity at different wavelengths. 17,29,30 Fig. 6(c) shows the photoresponse of heterojunction (fabricated by using 30 nm AZO on p-Si) as a function of wavelength under the forward bias condition.…”
Section: Resultsmentioning
confidence: 99%
“…This enhancement can be explained in the framework of different drifting of photogenerated electrons and holes in AZO and Si, respectively. 17,[29][30][31] For instance, the photogenerated electrons in AZO can easily move into Si due to a relatively low potential barrier at the interfacial region but the holes in Si cannot tunnel through the high potential barrier. 17,[29][30][31] Thus, it can be inferred that UV absorption enhances the performance of an AZO-based solar cell instead of leading to a much believed optical loss in the underlying absorbing layer.…”
Section: Resultsmentioning
confidence: 99%
“…In order to see this effect, various intermediate layers where deposited between the AZO and p-Si layers. It was found that the AZO/SiO 2 /p-Si heterojunction with SiO 2 as an insulating barrier displayed a good rectifying diode behavior [20,21]. Due to its rectifying behavior, we proceeded to investigate the following device structure with an AZO nanorod arrays grown on the AZO seed layer.…”
Section: Methodsmentioning
confidence: 99%